Health equity in urban and rural settings: implementation of the place standard tool in Spain - Ocaña-Ortiz, Ana; Gea-Caballero, Vicente; Juárez-Vela, Raúl; Peiró, Rosana; Pérez-Sanz, Elena; Santolalla-Arnedo, Iván; Sufrate-Sorzano, Teresa; Garrote-Cámara, María Elena; Paredes-Carbonell, Joan Josep (Frontiers in Public Health, 2024)
Physical, social, and economic aspects of neighborhoods and municipalities significantly influence residents' health behaviors and decisions, emphasizing the necessity of addressing local environmental disparities through an intersectoral, participatory, and equity-oriented approach. Community engagement is essential for gaining deeper insights into local contexts, integrating community knowledge and values, and fostering healthier, fairer, and equitable actions. The Place Standard Tool (PST) facilitates discussions on Social Determinants of Health, categorized into 14 themes, serving as a foundational framework for local health interventions. This study describes residents' perceptions of two municipalities in Spain, utilizing the validated Spanish version of the PST. A mixed-method convergent-parallel design was employed to comprehensively understand residents' experiences regarding their physical, economic, and social environment. A total of 356 individuals participated in the study through discussion groups, structured interviews, and online surveys. Descriptive analysis of individual questionnaire responses was conducted, and differences between municipalities were explored. Qualitative thematic analysis was performed on structured interviews and discussion groups, with quantitative and qualitative data integration facilitating comparison and identification of areas of convergence or divergence in the findings. Overall, rural areas garnered more favorable evaluations compared to urban ones, with Public Transport and Work and Local Economy consistently rated the lowest across all groups and contexts, while Identity and Belonging received the highest ratings. Notably, the urban area displayed additional negative ratings for Traffic and Parking, Housing, and Care and Maintenance. Identity and Belonging, Natural Spaces, Streets and Spaces, Social Interaction, and Services emerged as the highest-rated themes overall. In the rural context, positive evaluations were attributed to Walking or Cycling, Traffic and Parking, Housing, and Influence and Sense of Control. Significant differences (p <0.01) between urban and rural settings were observed in dimensions related to mobility, spaces, housing, social interaction, and identity and belonging. The study underscores the PST's efficacy in identifying strengths and weaknesses in local settings affecting health outcomes, highlighting the significance of successful implementation through appropriate territorial delineation. amd support from local authorities. Furthermore, the tool facilitated community involvement in decision-making about local environments, promoting equity by aligning institutional processes with citizen needs.